Carbon-coated current collector for prolonging cycle life of battery, preparation method of carbon-coated current collector, positive plate and battery
By using the carbon coated current collector prepared by modified hydrophilic carbon black on the current collector of the lithium-ion battery, the problem of insufficient cycle life and stability of the lithium-ion battery is solved, and higher cycle stability and longer cycle life are achieved.
Patent Information
- Application Number
- CN202510026648.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
During the cycle charging and discharging process of existing lithium-ion batteries, the cycle life is short and the cycle stability is poor. The existing technology mainly focuses on improving positive and negative electrode materials, and ignores the optimization of current collectors.
Modified hydrophilic carbon black is prepared by mixing 3,3'-diaminobenzidine and carbon black in a concentrated nitric acid solution, and mixed it with polytetrafluoroethylene and water, adding isopropanol to form a carbon coating slurry and coated on the current collector to produce an improved carbon coating current collector.
The cycle stability and cycle life of lithium-ion batteries are improved. By forming modified hydrophilic carbon black, the ion adsorption and diffusion rate of carbon black are enhanced, and the binding force between the carbon coating layer and the positive electrode material is enhanced.
Smart Images

Figure CN119812354A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-coated current collector for improving the cycle life of a battery, a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] In recent years, lithium-ion batteries have gradually become a research hotspot due to their advantages such as high specific capacity, high charge and discharge efficiency, good cycle performance and low cost. With the rapid development of electronic products and new energy vehicle technology, as well as the widespread application of lithium-ion batteries in military equipment, aerospace and other fields, higher requirements have been put forward for the quality and performance of lithium-ion batteries. Among them, the cycle life and cycle stability of batteries are particularly important. The cycle life of a battery refers to the number of times a battery can maintain a certain performance standard during repeated charge and discharge; cycle stability refers to whether the electrochemical properties of the material can remain stable after multiple charge and discharge cycles.
[0003] At present, most battery manufacturers have devoted a lot of research work on the topic of extending the cycle life of batteries, but they mainly focus on improving the characteristics of the positive and negative active materials of the batteries to improve the cycle life of the batteries, while ignoring the optimization and improvement of other battery components such as the battery current collector. Summary of the invention
[0004] The present invention provides a carbon-coated current collector and a preparation method thereof, a positive electrode sheet and a battery, aiming to improve the cycle life of a lithium-ion battery and ensure its cycle stability.
[0005] To achieve the above purpose, the technical solution provided by the present invention is:
[0006] The first aspect of the present application provides a method for preparing a carbon-coated current collector for improving the cycle life of a battery, comprising the following steps:
[0007] Step S1: mixing 3,3'-diaminobenzidine and carbon black in a concentrated nitric acid solution and subjecting them to heat treatment to obtain modified hydrophilic carbon black;
[0008] Step S2: uniformly mixing the modified hydrophilic carbon black, polytetrafluoroethylene and water, then adding isopropanol and stirring uniformly to obtain a carbon coating slurry;
[0009] Step S3: allowing the carbon-coated slurry to form a carbon-coated layer on the current collector to obtain a carbon-coated current collector.
[0010] In order to optimize the above technical solutions, the specific limitations adopted also include:
[0011] Furthermore, in step S1, the mass ratio of the 3,3'-diaminobenzidine to the carbon black is 1-3:7-8; the concentration of the concentrated nitric acid solution is 7.5-8 mol / L, and the amount of the concentrated nitric acid solution used is more than 15 times the mass of the carbon black.
[0012] Furthermore, in step S1, the reaction temperature of the mixed heat treatment of 3,3'-diaminobenzidine and carbon black in a concentrated nitric acid solution is 120-140°C, and the reaction time is 8-18h.
[0013] Furthermore, in step S1, the product after heat treatment is filtered, washed and vacuum dried to obtain modified hydrophilic carbon black; the vacuum drying conditions are: drying in a vacuum drying oven at 75-85° C. for 12-24 hours.
[0014] Furthermore, in step S2, the mass ratio of the modified hydrophilic carbon black to polytetrafluoroethylene and isopropanol is 3.2-4.6:1-1.3:0.4-0.6; and the solid content of the carbon coating slurry is 9-13wt%.
[0015] Furthermore, in step S2, the carbon coating slurry is coated on the current collector to form a carbon coating layer by coating method, and the process conditions are: coating speed 30-60m / min, single layer coating surface density 0.3-0.6g / m 2 .
[0016] Preferably, the carbon black is Vulcan XC-72 carbon black.
[0017] The second aspect of the present application provides a carbon-coated current collector prepared by the above method for improving the cycle life of the battery.
[0018] The third aspect of the present application provides a positive electrode sheet, comprising the above-mentioned carbon-coated current collector for improving the battery cycle life.
[0019] A fourth aspect of the present application provides a battery comprising the above-mentioned positive electrode sheet.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention modifies and compounds the carbon-coated slurry with concentrated nitric acid and 3,3'-diaminobenzidine, and uses the carbon-coated slurry to form a carbon-coated layer on a current collector to obtain an improved carbon-coated current collector. The lithium-ion battery assembled using the carbon-coated current collector has excellent cycle stability and a long cycle life.
[0022] In the preparation of the carbon coating slurry of the present invention, 3,3'-diaminobenzidine and carbon black are first mixed and heat-treated in a concentrated nitric acid solution to obtain a modified hydrophilic carbon black. The modified hydrophilic carbon black of the present application has multiple advantages:
[0023] Concentrated nitric acid solution can improve the hydrophilicity of the carbon fiber surface, and the strong oxidation effect can also enhance its surface polarity, increase the oxygen functional groups and specific surface area on the carbon fiber surface, and improve the chemical application effect of carbon fiber;
[0024] The formation of modified hydrophilic carbon black is beneficial to expand the interlayer distance of carbon black molecules, thereby enhancing the adsorption and accommodation of carbon black molecules to ions, and enabling carbon black to obtain higher ion conductivity and faster ion diffusion rate;
[0025] The composite modification with 3,3'-diaminobenzidine increases the active sites on the modified hydrophilic carbon black molecules, so that the modified hydrophilic carbon black can more fully react with the positive electrode material on the positive electrode sheet, and the binding force between the carbon coating slurry and the positive electrode material is enhanced to form a stable polymer chain, which can optimize the cycle stability and cycle life of the manufactured battery.
[0026] In the preparation of the carbon coating slurry of the present invention, the modified hydrophilic carbon black, polytetrafluoroethylene and water are mixed and then isopropanol is added to obtain the carbon coating slurry. The addition of polytetrafluoroethylene in an appropriate proportion mainly plays a bonding role and improves the viscosity of the slurry so that it can be better coated on the aluminum foil; the appropriate proportion of isopropanol can increase the wettability of the slurry so that the slurry is not viscous or solid, and its fluidity is enhanced. The later addition of isopropanol can avoid the occurrence of star points and gray points on the film surface during the coating process of the slurry, so that the film surface is smoother.
[0027] The carbon black of the present invention preferably uses Vulcan XC-72 carbon black because it has a finer particle size, good dispersibility, can improve surface smoothness and maintain the mechanical properties of the polymer, so the composite modification effect with 3,3'-diaminobenzidine is better, and the cycle stability and cycle life of the battery are better promoted. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : Schematic diagram of the preparation process of the carbon-coated current collector for improving the battery cycle life of the present invention. DETAILED DESCRIPTION
[0029] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.
[0030] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.
[0031] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.
[0032] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0033] The present application provides a method for preparing a carbon-coated current collector for improving the cycle life of a battery, such as Figure 1 As shown, the following steps are included:
[0034] Step S1: mixing 3,3'-diaminobenzidine and carbon black in a concentrated nitric acid solution and subjecting them to heat treatment to obtain modified hydrophilic carbon black;
[0035] Step S2: uniformly mixing the modified hydrophilic carbon black, polytetrafluoroethylene and water, then adding isopropanol and stirring uniformly to obtain a carbon coating slurry;
[0036] Step S3: The carbon-coated slurry is used to form a carbon-coated layer on the current collector to obtain a carbon-coated current collector.
[0037] In some embodiments, in step S1, the mass ratio of 3,3'-diaminobenzidine to carbon black is 1-3:7-8; the concentration of the concentrated nitric acid solution is 7.5-8 mol / L;
[0038] The amount of concentrated nitric acid used is excessive, and the amount of concentrated nitric acid solution used is more than 15 times the mass of carbon black. Preferably, the amount of concentrated nitric acid solution used is about 20 times the mass of carbon black.
[0039] In some embodiments, in step S1, the reaction temperature for heat treatment of 3,3'-diaminobenzidine and carbon black in a concentrated nitric acid solution is 120-140°C, and the reaction time is 8-18 hours.
[0040] In some embodiments, in step S1, the product after heat treatment is filtered, washed, and vacuum dried to obtain modified hydrophilic carbon black; the vacuum drying conditions are: drying in a vacuum drying oven at 75-85° C. for 12-24 hours.
[0041] Pure water is used for washing and filtering, and excessive pure water is used for washing and filtering multiple times.
[0042] In some embodiments, in step S2, the mass ratio of modified hydrophilic carbon black to polytetrafluoroethylene and isopropanol is 3.2-4.6: 1-1.3: 0.4-0.6; and the solid content of the carbon coating slurry is 9-13wt%.
[0043] In some embodiments, in step S2, the carbon coating slurry is coated on the current collector to form a carbon coating layer by coating method, and the process conditions are: coating speed 30-60m / min, single layer coating surface density 0.3-0.6g / m 2 .
[0044] The carbon-coated slurry is used to form a carbon-coated layer on the current collector to prepare the carbon-coated current collector. The above coating method is not limited to the above coating method, and various optional methods such as spraying method, transfer method, etc. can also be used.
[0045] Preferably, the carbon black is Vulcan XC-72 carbon black.
[0046] The present application also provides a carbon-coated current collector prepared by the above method for improving the cycle life of the battery.
[0047] The present application also provides a positive electrode sheet, comprising the above-mentioned carbon-coated current collector for improving the battery cycle life.
[0048] The present application also provides a battery, comprising the above-mentioned positive electrode sheet.
[0049] In some embodiments, the battery preparation process is as follows:
[0050] Preparation of negative electrode sheet: evenly apply the negative electrode slurry on the negative electrode current collector, remove the slurry solvent spread on the substrate by drying and heating in an oven, so that the solid material is well bonded to the substrate to prepare the negative electrode material, and then perform corresponding rolling, slitting, die-cutting, drying, and pole ear welding and encapsulation to finally obtain the corresponding negative electrode sheet;
[0051] Preparation of positive electrode sheet: coating the positive electrode slurry on the carbon-coated current collector prepared in the present application, removing the slurry solvent spread on the substrate by drying and heating in an oven, so that the solid material is well bonded to the substrate, preparing the positive electrode material, and then performing corresponding rolling, slitting, die-cutting, drying, and pole ear welding and encapsulation to finally obtain the corresponding positive electrode sheet;
[0052] Preparation of batteries: The positive electrode sheet, negative electrode sheet and separator are wound or stacked in a certain order (positive electrode sheet-separator-negative electrode sheet-separator) to form the preliminary structure of the battery cell. The wound or stacked battery cell is then placed in the battery shell. The battery shell is then sealed to ensure the sealing between the battery cell and the battery shell. Finally, the electrolyte is injected into the battery shell to provide an ion conduction medium for the battery.
[0053] Among them, the preparation of negative electrode slurry, positive electrode slurry and electrolyte can adopt various optional schemes in the art without limitation.
[0054] The negative electrode current collector in the following specific embodiments is copper foil, but the application of the solution of the present application is not limited thereto.
[0055] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments:
[0056] Embodiment 1:
[0057] Preparation of a carbon-coated current collector, a positive electrode sheet and a battery:
[0058] (1) The preparation process of the carbon-coated current collector includes the following processes:
[0059] Step S1: Preparation of modified hydrophilic carbon black: 140 g of Vulcan XC-72 carbon black and 20 g of 3,3'-diaminobenzidine were mixed and added into 2800 g of 67 wt% concentrated nitric acid, and the mixture was heated in an oil bath at 140° C. for 10 h. The mixture was filtered and washed with pure water, and then vacuum dried at 80° C. to finally obtain modified hydrophilic carbon black.
[0060] Step S2: Preparation of coating slurry: 120 g of modified hydrophilic carbon black, 30 g of polytetrafluoroethylene and deionized water were mixed evenly, 13 g of isopropanol was added, and stirred evenly to obtain a coating slurry with a solid content of 9.2 wt %;
[0061] Step S3: Preparation of carbon-coated aluminum foil: Coat the coating slurry on the surface of the aluminum foil (coating speed 50 m / min, single-layer coating surface density 0.75 g / m 2 ), and after drying (drying temperature is 80° C.), a carbon-coated aluminum foil, i.e., a carbon-coated current collector, is obtained;
[0062] (2) The preparation process of the positive electrode sheet and the battery includes the following processes:
[0063] Step 1: Preparation of negative electrode sheet: Graphite, styrene butadiene rubber, carboxymethyl cellulose, conductive agent and pure water are mixed evenly to obtain negative electrode slurry (the mass ratio of graphite, styrene butadiene rubber, carboxymethyl cellulose, conductive agent and pure water is 93.2:1.6:2.3:2.7:2.08, the negative electrode slurry is coated on copper foil, baked at 140°C for 10 hours, and rolled to obtain a negative electrode sheet (compacted density is 1.23g / cc);
[0064] Step 2: Preparation of positive electrode sheet: The ternary active material NCM811, the conductive agent, polyvinylidene fluoride and N-methylpyrrolidone are mixed evenly to obtain a positive electrode slurry (the mass ratio of the ternary active material NCM811, the conductive agent, polyvinylidene fluoride and N-methylpyrrolidone is 91:4.2:4.4:2.53); the positive electrode slurry is coated on the prepared carbon-coated current collector, baked at 140°C for 10 hours, and rolled to obtain a positive electrode sheet (the compaction density is 2.35g / cc);
[0065] Step 3: Preparation of electrolyte: Ethylene carbonate and ethyl methyl carbonate are mixed evenly in a volume ratio of 3:7, and lithium hexafluorophosphate is added and mixed evenly to obtain an electrolyte with a concentration of 0.5 mol / L;
[0066] Step 4: Preparation of the battery: Wind or stack the anode, cathode and diaphragm (PE film) in a certain order (positive electrode-diaphragm-negative electrode-diaphragm) to form the preliminary structure of the battery cell; then put the wound or stacked battery cell into the battery shell; then seal the battery shell to ensure the sealing between the battery cell and the battery shell; finally, inject electrolyte into the battery shell to provide an ion conduction medium for the battery, and finally assemble it into a lithium-ion battery.
[0067] Embodiment 2:
[0068] Compared with Example 1, the mass ratio of Vulcan XC-72 carbon black to 3,3'-diaminobenzidine in step S1 of Example 2 is 7:1.5, and the other steps are the same as Example 1.
[0069] Embodiment 3:
[0070] Compared with Example 1, the mass ratio of Vulcan XC-72 carbon black to 3,3'-diaminobenzidine in step S1 of Example 3 is 7:2, and the other steps are the same as Example 1.
[0071] Embodiment 4:
[0072] Compared with Example 1, the mass ratio of Vulcan XC-72 carbon black to 3,3'-diaminobenzidine in step S1 of Example 4 is 7:2.5, and the other steps are the same as Example 1.
[0073] Embodiment 5:
[0074] Compared with Example 1, the mass ratio of Vulcan XC-72 carbon black to 3,3'-diaminobenzidine in step S1 of Example 5 is 7:3, and the other steps are the same as Example 1.
[0075] Comparative Example 1:
[0076] Compared with Example 1, in Comparative Example 1, the concentrated nitric acid in step S1 is replaced by acetic acid, and the other steps are the same as those in Example 1.
[0077] Comparative Example 2:
[0078] Compared with Example 1, in step S1 of Comparative Example 2, 3,3'-diaminobenzidine is not added, and the other steps are the same as those of Example 1.
[0079] Comparative Example 3:
[0080] Compared with Example 1, in step S1 of Comparative Example 3, Vulcan XC-72 carbon black is not subjected to modification pretreatment and is directly used, and the other steps are the same as those of Example 1.
[0081] Comparative Example 4:
[0082] Compared with Example 1, the mass ratio of Vulcan XC-72 carbon black to 3,3'-diaminobenzidine in step S1 of Comparative Example 4 is 7:4, and the other steps are the same as those in Example 1.
[0083] Comparative Example 5:
[0084] Compared with Example 1, the mass ratio of Vulcan XC-72 carbon black to 3,3'-diaminobenzidine in step S1 of Comparative Example 5 is 7:6, and the other steps are the same as those in Example 1.
[0085] The purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and exemplarily include: carbon black: brand Vulcan XC-72 (imported from the United States), purchased from Suzhou Shengernuo Technology Co., Ltd.; 3,3'-diaminobenzidine, purchased from Sinopharm Chemical Reagent Co., Ltd.; aluminum foil: 12 μm thick, brand H18-1100, purchased from Shenzhen Honglei Metal Materials Co., Ltd.; positive electrode active material: lithium iron phosphate, Defang Nano DF5F; binder polytetrafluoroethylene and polyvinylidene fluoride, purchased from Shanghai Huahenghui New Materials Technology Co., Ltd.; conductive agent: conductive carbon black SUPER P Li (Swiss Termega), purchased from Guangdong Lvwei New Materials Technology Co., Ltd.; copper foil: T2 copper foil, 8 μm thick, purchased from Shandong Huiya Metal Technology Co., Ltd.; battery case: model CR2032, purchased from Taizhou Yajun Battery Materials Co., Ltd.; diaphragm: PE film, 20 μm thick, purchased from Dongguan Xuecheng Plastic Products Co., Ltd.; lithium sheet: purchased from Dongguan Liren New Materials Technology Co., Ltd.; gasket: 304 stainless steel disc, purchased from Wuxi Yiri New Materials Technology Co., Ltd.; spring: item number 2032, purchased from Xinghua Benoite Battery Materials Co., Ltd.
[0086] Battery assembly: lithium iron phosphate, polyvinylidene fluoride, a conductive agent and N-methylpyrrolidone are mixed evenly to obtain a positive electrode material slurry (the overall solid content of the positive electrode slurry is 45%); the positive electrode material slurry is coated on the surface of the carbon-coated current collector obtained in the embodiment and the comparative example, and vacuum dried at 110°C for 18 hours, and rolled to obtain a positive electrode sheet; in an inert gas atmosphere, the button battery is assembled in the following order: battery shell - placing positive electrode sheet - dripping electrolyte - placing diaphragm - dripping electrolyte - placing lithium sheet - placing gasket shrapnel - battery shell.
[0087] The Wuhan Blue Electric Test System (CT3002A) was used to conduct the corresponding cycle life test and stability test on the button battery. The constant current charge and discharge test was carried out at different current densities (0.1, 0.5, 1, 2, 4A g -1 ) was used for cycle testing, and the voltage cutoff range was set to 1.8-4.1V.
[0088] Cycle life: Start the test equipment and start the constant current charge and discharge test. Charge test: Initially charge the battery at the specified test environment temperature until the specified charge cut-off voltage is reached. Discharge test: Discharge the battery at the specified discharge current until the specified discharge cut-off voltage is reached. Cycle test: Perform multiple charge and discharge cycle tests on the battery according to the above steps. The number of cycles is usually set to 3000.
[0089] Cycle capacity retention rate: During the cycle test, record the corresponding charge / discharge capacity of each cycle. The specific calculation formula is: Capacity retention rate = (end capacity / initial capacity) × 100%. Initial capacity: refers to the rated capacity of the battery during the test (i.e. the first charge and discharge cycle). End capacity: refers to the remaining capacity of the battery at the end of a certain cycle after a certain number of charge and discharge cycles.
[0090] The examples and comparative examples were tested and the results are shown in Table 1:
[0091] Table 1 Comparison of cycle performance test results of various embodiments and comparative examples
[0092] Cycle life / capacity retention <![CDATA[0.2A g -1 ]]> <![CDATA[1A g -1 ]]> <![CDATA[4A g -1 ]]> Example 1 1200 cycles (96.4%) 1000 cycles (95.1%) 920 cycles (93.7%) Example 2 1400 cycles (98.1%) 1240 cycles (96.8%) 1080 cycles (95.1%) Example 3 1160 cycles (95.6%) 970 cycles (94.2%) 910 cycles (93.7%) Example 4 1000 cycles (94.2%) 870 cycles (92.7%) 840 cycles (90.6%) Example 5 950 cycles (93.4%) 750 cycles (91.9%) 680 cycles (89.7%) Comparative Example 1 400 cycles (86.1%) 300 cycles (83%) 200 cycles (79.9%) Comparative Example 2 670 cycles (91%) 620 cycles (87%) 515 cycles (84%) Comparative Example 3 400 cycles (85.4%) 300 cycles (80.9%) 220 cycles (70.1%) Comparative Example 4 800 cycles (75.4%) 690 cycles (70.9%) 540 cycles (62.1%) Comparative Example 5 609 cycles (65.4%) 502 cycles (60.9%) 420 cycles (54.1%)
[0093] This application can draw the following conclusions from the test data in Table 1 above after analysis and research:
[0094] In Comparative Example 1, the concentrated nitric acid in step S1 is replaced with acetic acid, which loses the strong oxidizing effect of concentrated nitric acid on carbon black, and the modification effect of acetic acid on carbon black is weak. In this case, even if 3,3'-diaminobenzidine is introduced, the performance of the prepared battery is still poor.
[0095] In step S1 of comparative example 2, 3,3'-diaminobenzidine is not added, and only concentrated nitric acid has a modification effect on carbon black. Although the data is slightly better than that of comparative example 1, the battery prepared by this scheme still cannot achieve a better cycle performance level.
[0096] In step S1 of comparative example 3, Vulcan XC-72 carbon black was used directly without modification pretreatment, and the result was similar to that of comparative example 1.
[0097] The mass ratios of Vulcan XC-72 carbon black and 3,3'-diaminobenzidine in Comparative Examples 4 and 5 are 7:4 and 7:6. The carbon-coated slurry prepared at this ratio will precipitate during the coating process, which is not conducive to coating. At the same time, the applied coating will gradually fall off over time, resulting in lower performance of the carbon-coated aluminum foil current collector, which ultimately leads to decreased cycle stability of the assembled lithium-ion battery and easy short circuit. Therefore, the mass ratio of Vulcan XC-72 carbon black and 3,3'-diaminobenzidine must be greater than 2.
[0098] The present invention uses concentrated nitric acid solution to modify carbon black. The strong oxidizing effect of concentrated nitric acid can change the properties of carbon black molecules, increase the pore spacing and interlayer spacing of carbon black molecules, enhance their surface polarity, increase the oxygen functional groups and specific surface area on the carbon fiber surface, and improve the chemical application effect of carbon fiber.
[0099] Concentrated nitric acid can provide more favorable conditions for the chemical polymerization reaction of 3,3'-diaminobenzidine and carbon black; and the introduction of 3,3'-diaminobenzidine can increase the active sites on the modified hydrophilic carbon black molecules, so that the modified hydrophilic carbon black can more fully react with the positive electrode material on the positive electrode sheet, and the binding force between the carbon-coated slurry and the positive electrode material is enhanced to form a stable polymerization chain, thereby improving the cycle stability and cycle life of the battery.
[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon-coated current collector for improving battery cycle life, characterized in that: The following steps are involved: Step S1: mixing 3,3'-diaminobenzidine and carbon black in a concentrated nitric acid solution and subjecting them to heat treatment to obtain modified hydrophilic carbon black; Step S2: uniformly mixing the modified hydrophilic carbon black, polytetrafluoroethylene and water, then adding isopropanol and stirring uniformly to obtain a carbon coating slurry; Step S3: allowing the carbon-coated slurry to form a carbon-coated layer on the current collector to obtain a carbon-coated current collector.
2. The method for preparing a carbon-coated current collector for improving battery cycle life according to claim 1, characterized in that: In step S1, the mass ratio of 3,3'-diaminobenzidine to carbon black is 1-3:7-8; the concentration of the concentrated nitric acid solution is 7.5-8 mol / L, and the amount of the concentrated nitric acid solution used is more than 15 times the mass of the carbon black.
3. The method for preparing a carbon-coated current collector for improving battery cycle life according to claim 1, characterized in that: In step S1, the reaction temperature of heat treatment of 3,3'-diaminobenzidine and carbon black mixed in concentrated nitric acid solution is 120-140°C, and the reaction time is 8-18h.
4. The method for preparing a carbon-coated current collector for improving battery cycle life according to claim 1, characterized in that: In step S1, the product after heat treatment is filtered, washed and vacuum dried to obtain modified hydrophilic carbon black; the vacuum drying conditions are: drying in a vacuum drying oven at 75-85° C. for 12-24 hours.
5. The method for preparing a carbon-coated current collector for improving battery cycle life according to claim 1, characterized in that: In step S2, the mass ratio of the modified hydrophilic carbon black to polytetrafluoroethylene and isopropanol is 3.2-4.6:1-1.3:0.4-0.6; The solid content of the carbon coating slurry is 9-13wt%.
6. The method for preparing a carbon-coated current collector for improving battery cycle life according to claim 1, characterized in that: In step S2, the carbon coating slurry is coated on the current collector to form a carbon coating layer by coating method, and the process conditions are: coating speed 30-60m / min, single layer coating surface density 0.3-0.6g / m 2 .
7. The method for preparing a carbon-coated current collector for improving battery cycle life according to claim 1, characterized in that: The carbon black is Vulcan XC-72 carbon black.
8. A carbon-coated current collector for improving battery cycle life prepared by the method according to any one of claims 1 to 7.
9. A positive electrode sheet, characterized in that: A carbon-coated current collector for improving battery cycle life as claimed in claim 8.
10. A battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Synthesis process of medical and chemical intermediate 3,3'-dinitro-4,4'-diacetylbiphenyldiamine
CN106631866A
Preparation method of alkaline zinc-iron flow battery
CN113113620A
Silicon-based composite negative electrode material and preparation method thereof
CN115101730A
Safe prime coat slurry for lithium ion battery, preparation method of safe prime coat slurry and current collector
CN115895368A
Shoes cover with eison and manufacturing method thereof
KR1020210089279A